Impact of climate change on food production in Kenya - Amos Otieno Wanjara; Paul Okeyo Ogembo (Journal of Environment and Sustainability Education, 2026)
Climate Change Phenomena has posed a serious threat toward food production with ramifications on; food security, human and livestock lives.  This has led to dozens of Global Climate Summits to address the subject. The objectives of the study were to establish effects of climate change on grain crop production and livestock production in Kenya. Methodology was anchored on the work of Ferrer (1998), through which a meta-analysis of 39 empirical studies were done. The findings indicated that Climate Change occasioned by extreme weather events like La Nino (prolonged droughts) and El Nino (Rains Above normal annual average) have negative impacts on food and livestock production in Kenya.  High incidence of human and livestock diseases also occurs. Weather extremes, with serious repercussions on crop and livestock production have been reported in Kenya during the 2021/2022, 2023/2024 calendar years. Climate change make the naturally drier areas suffer flash floods and other associated challenges. It negatively impacts livestock rearing and food crop production especially in the Argo-Ecological zones of medium to low rainfall amounts of Arid and Semi-Arid lands. The findings have implications for essential mitigation/adaptation strategies including; crop diversification, planting of drought resistant food crops, improved seeds and diversified socio-economic livelihoods, towards improving food and livestock production in Kenya and possible remedies and resilience towards coping with the phenomenon.